Fractional slot concentrated winding PM synchronous motors for transport electrification applications - Shaohong, Zhu (2021)
Moving towards electrification of transport including electric vehicles (EV), more electric aircraft (MEA), and electric ships offers a crucial way in dealing with global carbon emissions and climate change. Electric motors are a key enabling technique in these applications, but their increased use is associated with requirements of extreme power/torque density, excellent fault-tolerance, high efficiency, and good manufacturability. The main goal of this thesis is to study permanent magnet electric machine winding theory to determine the suitable electric machine winding topologies for different applications. Two separate vehicle transport applications are investigated, including an EV traction motor and a novel modular electromechanical actuator (EMA) for MEA. The study of the EV traction motor involves the investigation of methods for reducing the significant stator MMF harmonics in fractional slot concentrated winding (FSCW) electric machines, and the development of novel FSCW topologies while keeping the benefits of easy manufacturing and the non-overlapping characteristic of concentrated windings. The novel FSCW topologies can be extended to multi-phase FSCW motors. A traction motor equipped with a novel 24 slots, 14 poles FSCW topology and interior PM (IPM) rotor is developed for evaluation. The performance under normal and fault conditions is fully explored and validated with simulation and experimental results, which demonstrates the applicability and strong potential of the proposed 24 slots, 14 poles IPM motor in fault-tolerant traction motor applications. The second topic focuses on modular fault-tolerant EMAs for aircraft actuation systems which can meet a diverse range of requirements. The architecture and design considerations of the actuator system are firstly determined considering reliability, fault-tolerance, and weight. The modular EMA scheme consisting of a direct-drive rotary motor and mechanical screw is identified. A dual 3-phase 24 slots, 22 poles FSCW motor with a surface-mounted permanent magnet (SPM) rotor is developed and evaluated in terms of electromagnetics, thermal management, and fault-tolerance. Experimental results of the modular EMA motor prototypes agree well with predicted results. All this confirms the applicability and satisfactory implementation of the modular EMA motor for aircraft actuation system applications.